Engineering Sciences in Philosophical Perspective: Ontology, Epistemology, and Ethics. - Wang, Dazhou; Kazakova, Aleksandra (NanoEthics, 2026)
The growth and dissemination of scientific knowledge are characteristic of contemporary engineering worldwide. In recent decades, the distinctive features of engineering sciences have been discussed in comparison to both the natural sciences and other forms of knowledge circulating in engineering practice. The range of problems in the philosophy of engineering sciences includes, for example, the relationship between theory and practice; the processes of explaining and formalising knowledge; the demarcation between natural sciences and engineering sciences and their interaction in technoscience; the emergence and formation of branches of engineering science and their mutual influence; the development of engineering science disciplines in different national contexts; the logic and structure of engineering research; multi- and interdisciplinary research methodologies; the nature of engineering systems thinking and ontologies; the functions of languages, visualizations and artefacts; the problems of digitisation and the application of Artificial Intelligence in engineering research; as well as specific questions of experimentation, modelling, quantification, etc. The special collection invites contributions from philosophy of engineering, STS and engineering studies, engineering ethics, and related fields, as well as methodological research in engineering education, including comparative studies and case studies.